MSMEs Empowerment through Digital Innovation: The Key to Success of E-Commerce in Indonesia - Willya Achmad (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
The growth of digital technology and the adoption of e-commerce have provided new opportunities for MSMEs to expand their market reach and increase their competitiveness. However, despite their potential, there are still many MSMEs in Indonesia who experience difficulties in implementing e-commerce and making optimal use of digital innovation. This study aims to analyze the role of digital innovation in empowering Micro, Small and Medium Enterprises (MSMEs) in Indonesia through the implementation of e-commerce. This research will use a qualitative approach by conducting case studies of a number of MSMEs in Indonesia that have successfully implemented digital innovation in their operations. The results of this study are expected to provide a better understanding of the role of digital innovation in empowering MSMEs in Indonesia through e-commerce. In addition, this research is also expected to be able to identify the challenges and obstacles faced by MSMEs in adopting digital innovation, as well as provide policy recommendations and strategies to increase the accessibility and success of e-commerce for MSMEs in Indonesia.